Shariah issues in managing household debt: the case of Malaysia - Maznita Mokhtar; Azman Ismail (Penerbit Universiti Kebangsaan Malaysia, 2013)
The Edge Malaysia, in its 2011 publication, projects there will be 68,000 high net worth individuals (HNWI) in a population of 19.2 million by 2015. This means there will be one HNWI for every 282 persons in Malaysia. Hence, the Islamic wealth management industry is placing greater emphasis on wealth accumulation and preservation products vis-à-vis investment funds and assets. In their chase for HNWI clientele, financial institutions seem to neglecta fundamental stage of the Islamic wealth management process, namely wealth creation. In Islam, rizq is translated as subsistence or the means to live. In their search for income to meet their livelihood, Muslims need to ensure that their household’s wealth effect adhere to Shariah by linking the level of personal wealth to the spending or saving decisions. In recent years, household indebtedness in Malaysia has grown from 33% of banking sector loans in 1998 to 55% in 2011, representing 76.6% of the GDP. The cause for concern stems from the revelation that this growing pattern of debt is driven by personal consumption that is mismatched against income growth. The present paper provides an overview of the household debt situation in the Malaysia. In particular, the present study examines the concerns over the growing trend of Malaysian indebtedness from the perspective of consumers and evaluates consumer issues in seeking Islamic financing (personal and consumptive)products to meet livelihood needs. The paper offers suggestions for improvements in relevant products and development within the Malaysian wealth management landscape in light of maqasid al-Shariah.